The different shades of autism the screening and diagnosis of autistic spectrum disorders - Veronica Bird Charitable Foundation (Riva, MD : Veronica Bird Charitable Foundation, 2003)
(Producer) Explains signs of autism, differentiation between types of autistic disorders, infantile versus regressive forms, testing procedures, and early referral and intervention
Copyright date on credit frame: 2000; copyright date on container: 2003
VHS
Keywords: Autistic Disorder -- diagnosis